Mangifera indica kernel phytochemicals, a potent remedy for oral-dental infections (Funded Work) - SAVITA PETWAL; MADHURI KAUSHISH LILY; HIMANI SINGH; KOUSHALYA DANGWAL (International Journal of Pharma and Bio Sciences, 2019)
This study evaluates the anti-bacterial potential of M. indica twig and kernel phytochemicals against the common oral bacterial pathogens including S. aureus, St. oralis, St. mutans, St. gordonii, L. brevis and L. casei. The twig and kernel dried powder samples were fractionated with Soxhlet extractor with eluotrophic series of solvents viz. petroleum-ether, chloroform, absolute-ethanol, 80%-methanol and distilled-water. Antibacterial activity of the fractionated extracts was determined by zone of inhibition, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and 50% inhibitory concentration (IC50) values against oral pathogens while antioxidant activity was measured by ABTS+ and DPPH assays. The results showed exceptionally high antibacterial activity in kernel ethanolic extracts (MiKE) against all the tested oral bacterial pathogens as confirmed by its highest zone of inhibition and lowest MIC, MBC and IC50 values. M.indica kernel extracts (MiKE) was extremely effective against S. aureus followed by St. oralis, St. gordonii, L. brevis, St. mutans, and L. casei with the IC50 value of 0.015, 0.027, 0.056, 0.081, 0.108±0.003 and 0.122±0.001 mg/ml respectively. MiKE showed excellent ABTS+ and DPPH free radical scavenging activities with IC50 values of 0.649±0.0 and 0.264±0.001 µg/ml respectively amid abundance of phenolics, flavanoids and tannins. Regression analysis of antibacterial activities of fractionated extracts with phytochemical contents and antioxidant activities suggested existence of multiple pathways of inhibition in bacteria. Present study successfully establishes M. indica kernel extracts as an incredible and safe prospective natural remedy for oral-dental infection.